The Management’s Motives of Income Smoothing and Its Implications to The Market Reaction (Jurnal Dinamika Akuntansi, 2021)
Purpose: The study is aimed to examine the motive behind income smoothing includes oportunistic behaviour of management, financial distress, and capital structure to the market response of manufacturing companies which are listed in Indonesia Stock Exchange in 2014-2018 periods. Methodology: The sample collection technique has been done by using purposive sampling method, and based on the predetermined criteria, the total data observations are 591. The data analysis technique has been done by using path analysis with 24rd AMOS tool.Findings: Based on the result of hypothesis test, it can be concluded that financial distress has a positive effect to the income smoothing, oportunistic behaviour of management has a negative effect to the income smoothing, capital structure has no significant effect to income smoothing, oportunistic behaviour of management has a positive effect to the market response, financial distress, capital structure and income smoothing has no significant effect to the market response income smoothing cannot be intervening variable between the influence of oportunistic behaviour of management, financial distress, and capital structure to the market response Novelty: The difference between this study with another research is: 1) this study focused on the influence of oportunistic behaviour of management, financial distress, and capital structure to the one of the earnings management that most frequently used, that is income smoothing; 2) this research also will examine the implication of each variable to the market response.